Enhancing the Performance of the Microwave Absorbing Materials by Using Dielectric Resonator Arrays. (5th April 2017) - Al-Zoubi, Omar H.; Naseem, Hameed
Abstract : We present a technique for enhancing the performance of microwave absorbing materials in terms of weight, thickness, and bandwidth. The introduced technique is based on fabricating the microwave absorbing (MA) material in a structure comprised of an array of circular cylinder dielectric resonators (CDR) backed by a perfect electric conductor (PEC) ground plane. Numerical electromagnetic methods are employed to study the properties of the proposed MA array structures, where 3D full wave simulation using finite-element method is implemented. The obtained results show that the performance of the MA-CDR arrays significantly outperforms that of a flat layer composed of the same material and having equivalent thickness. A flat layer of MA material with thickness of 5 mm backed by perfect electric conductor (PEC) shows as low as - 50 dB reflection loss (RL) peak and 3 GHz 10-dB bandwidth, whereas an MA-CDR array, composed of the same MA material, of height of 4 mm can achieve as low as −50 dB RL peak and 12 GHz 10-dB RL bandwidth.